Brasileiros em situação clandestina na Guiana Francesa: uma etnografia das relações e representações sociais entre migrantes - MARTINS, Rosiane Ferreira (Universidade Federal do Pará, 2014)
This dissertation explores the lives of clandestine Brazilian migrants who seek socioeconomic opportunities in French Guyana. The migrants’ discourse is used as a platform to reflect on the field of social representations in this context as well as the meaning of cohabitation in a pluriethnic and multicultural society where social subjects construct their identities from knowledge--without necessarily knowing one another--and difference. This ethnography, then, focuses on economic, social, and identitarian aspects of Brazilian mobility, and aims to analyze the experience of undocumented workers, the obstacles they face, and the strategies they deploy to move in the city and obtain work, food, accommodation, etc. This study builds upon fieldwork undertaken with Brazilian migration networks between the Brazilian border at the city Oiapoque and the police control leading to Cayenne.